Kewenangan Pemerintah Daerah dalam Penyelenggaraan Pengadaan Tanah Untuk Pembangunan Jalan Tol (Mimbar Keadilan, 2023)
This study aims to identify and understand the mechanism of land acquisition for development in the public interest, and to analyze the form of local government authority in implementing land acquisition for toll road construction. This type of research is normative legal research using statutory and conceptual approaches. Development is one of the efforts to achieve general welfare. In a development, land is definitely needed, while land owned by the state is getting less and less, so land acquisition is necessary. The implementation of land acquisition cannot be carried out arbitrarily, and the implementation of land acquisition for the public interest must pay attention to the interests of development and the interests of the community. The results of this study show that the government is the executor of land acquisition, the mechanism of which consists of four stages, namely planning, preparation, implementation, and the delivery of results. Then, the government and regional governments have the authority to guarantee the availability of land and funding for land acquisition for the public interest and as the executor of land acquisition. The government and regional governments have an obligation to prioritize the welfare of their citizens because the principle of development in the public interest is aimed at increasing the welfare of all people. The regional government is obliged to ensure that the assessment of compensation in land acquisition is based on the principles of fairness, benefit, agreement and sustainability.